IMPROVING THE ECONOMIC MECHANISM FOR THE DEVELOPMENT OF THE SERVICE SECTOR (Web of Technology: Multidimensional Research Journal, 2024)
The service sector has become a critical component of economic development, contributing significantly to GDP, employment, and societal well-being. This article explores the optimization of the economic mechanism for the development of the service sector. The study analyzes theoretical foundations, assesses current practices, and proposes innovative strategies to enhance efficiency and sustainability.